2015
DOI: 10.1371/journal.pone.0143782
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status Is an Independent Risk Factor for Global Cognitive Impairment in Peritoneal Dialysis Patients

Abstract: ObjectiveVitamin D (VD) deficiency is an independent risk factor for cognitive impairment (CI) in the general population, but VD status in peritoneal dialysis (PD) patients has not been investigated. In this study, we aimed to investigate the relationship between serum VD levels and global and specific cognitive functions in PD patients.Design and SettingCross-sectional study, simultaneously conducted at two PD centers.PatientsClinically stable patients (n = 273) undergoing PD for at least 3 months were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Our results regarding the extent of CI are similar to previous studies showing that CI is more common in those undertaking HD , in those who are older, and that CI was equally common in adequately dialysed peritoneal and HD patient groups . However, our results regarding the extent of CI in those undertaking peritoneal dialysis is higher than almost all previous studies published . We speculate that the variations from previous studies on the prevalence of CI in PD are the result of using different assessment tools or applying different study methods when using the MoCA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results regarding the extent of CI are similar to previous studies showing that CI is more common in those undertaking HD , in those who are older, and that CI was equally common in adequately dialysed peritoneal and HD patient groups . However, our results regarding the extent of CI in those undertaking peritoneal dialysis is higher than almost all previous studies published . We speculate that the variations from previous studies on the prevalence of CI in PD are the result of using different assessment tools or applying different study methods when using the MoCA.…”
Section: Discussionsupporting
confidence: 85%
“…35 However, our results regarding the extent of CI in those undertaking peritoneal dialysis is higher than almost all previous studies published. 12,14,[36][37][38] We speculate that the variations from previous studies on the prevalence of CI in PD are the result of using different assessment tools or applying different study methods when using the MoCA. For example, previous work by Shea et al 12 using the MoCA to screen for CI in those receiving PD in Hong Kong, utilized a cut-off of 21 or 22/30 based on previous validation studies in their setting, compared with a cut-off of ≤ 24/30 in this study.…”
Section: Discussionmentioning
confidence: 91%
“…10,11 Observational studies have found independent associations between the presence of 25-hydroxyvitamin D deficiency, hyperparathyroidism, untreated anaemia, cardiovascular disease and prior stroke with dialysis-associated MCI. [12][13][14][15][16] Associations with the parathyroid axis have been reinforced with postoperative improvements in cognitive and memory domains observed in patients undergoing surgery for secondary hyperparathyroidism, 17 though only in small studies. It is hoped that prospective longitudinal studies such as the Brain IN Kidney disease (BRINK) cohort may provide deeper mechanistic insights in the future.…”
Section: Diagnostic Definitions and Pathophysiologymentioning
confidence: 99%
“…In addition, in PD patients, low 25VD was found to be the independent factor for global cognitive impairment due to the antioxidant and neuroprotective role of 1,25VD. This is of crucial importance, as PD is a home-based renal replacement therapy that needs adequate cognition and self-monitoring [75].…”
Section: Muscle Health and Cognitive Functionmentioning
confidence: 99%